The Influence of Pedagogic Competence and Teacher Motivation on The Leadership Style of Principals at Nias Advent Private Junior High School - Jaya Adil Harefa; Laura Lahindah (PT. Publikasiku Academic Solution, 2024)
This research aims to analyze whether the principal's leadership style influences the pedagogical competence and motivation of teachers at Adventist Nias Private Middle School. The method used is qualitative. The research variables consist of: teacher pedagogical ability (X1), teacher motivation (X2), and leadership style (Y). This research was conducted at Nias Hilina'a Tafuo Adventist Private Middle School, Idanogawo District, Nias Regency, North Sumatra. This research uses a quantitative approach with a survey method with simple linear regression analysis. The results of the research, the calculated t value of the pedagogical competency variable is 2.376 > t table value 2.034 and the significant value is 0.024 < 0.05, so Ha is accepted and Ho is rejected, which means that the pedagogical competency variable has an effect on leadership style. The calculated t value of the motivation variable is 4,118 > t table value 2.034 and the significant value is 0.000 < 0.05, so Ho is rejected and Ha is accepted, which means that the motivation variable has an effect on leadership style.